Types of moral values found in yesterday movie - Legawa, I Gede Aditya Cipta; Jayantini, I Gusti Agung Sri Rwa; Pratiwi, Desak Putu Eka (Journal of Language and Applied Linguistics, 2022)
Moral values are concepts that serve as a guideline on implementing our manners, personalities, and behaviors toward ourselves and others. The movie is one of the best platforms to deliver moral values, it makes this study needed because it was found a lot of movie’s viewers only focused on fun things that existed in the movie than focused on the moral messages conveyed in it. The aim of this study is to tell the readers what moral values are, and the types of moral values, and help people in recognizing moral values that appear in the movie. This study used a descriptive qualitative method in analyzing the data and a documentation method used in collecting the data. As a result, there were eleven types of moral values that appeared in Yesterday movie, consisting of honesty, bravery, peace ability, confidence, purity & pureness, loyalty, respect, love & affection, sensitivity & selflessness, kind & friendly, and fair & humane. This finding shows that this comedy movie has many moral values to present.